High‐grade metamorphism and partial melting of basic and intermediate rocks - Palin, R; White, R; Green, E; Diener, J; Powell, R; Holland, T (Wiley, 2016)
Rocks of basic and intermediate bulk composition occur in orogenic terranes from all geological time periods and are thought to represent significant petrological components of the middle and lower continental crust. However, the former lack of appropriate thermodynamic models for silicate melt, amphibole and clinopyroxene that can be applied to such lithologies at high temperature has inhibited effective phase equilibrium modelling of their petrological evolution during amphibolite- and granulite facies metamorphism. In this work, we present phase diagrams calculated in the Na2O–CaO–K2O–FeO–MgO–Al2O3–SiO2–H2O–TiO2–O2 (NCKFMASHTO) compositional system for a range of natural basic and intermediate bulk compositions for conditions of 2–12 kbar and 600–1050 ∘C using newly parameterized activity–composition relationships detailed in a companion paper by Green et al. in this issue. Particular attention is given to mid-ocean ridge basalt (MORB) and diorite protolith bulk compositions. Calculated subsolidus mineral assemblages in all basic and intermediate rock types are modally dominated by hornblende and plagioclase, with variable proportions of epidote, clinopyroxene, garnet, biotite, muscovite, quartz, titanite or ilmenite present at different pressures. The H2O-saturated (wet) solidus has a negative P−T slope and occurs between ∼620–690 ∘C at mid- to lower-crustal pressures of 5–10 kbar. The lowest-T melts generated close to the wet solidus are calculated to have granitic major-element oxide compositions. Melting at higher temperature is attributed primarily to multivariate hydrate-breakdown reactions involving biotite and/or hornblende. Partial melt compositions calculated at 800–1050 ∘C for MORB show good correlation with analysed compositions of experimental glasses produced via hydrate-breakdown melting of natural and synthetic basic protoliths, with Niggli norms indicating that they would crystallize to trondhjemite or tonalite. Diorite is shown to be significantly more fertile than MORB and is calculated to produce high-T melts (>800 ∘C) of granodioritic composition. Subsolidus and suprasolidus mineral assemblages show no significant variation between different members of the basalt family, although the P−T conditions at which orthopyroxene stabilizes, thus defining the prograde amphibolite–granulite transition, is strongly dependent on bulk-rock oxidation state and water content. The petrological effects of open- and closed-system processes on the mineral assemblages produced during prograde metamorphism and preserved during retrograde metamorphism are also examined via a case-study analysis of a natural Archean amphibolite from the Lewisian Complex, northwest Scotland.